Charge-state assignment of nanoscale single-electron transistors from their current–voltage characteristics. Issue 31 (29th July 2019) - Limburg, Bart; Thomas, James O.; Sowa, Jakub K.; Willick, Kyle; Baugh, Jonathan; Gauger, Erik M.; Briggs, G. Andrew D.; Mol, Jan A.; Anderson, Harry L.
Abstract : The charge state of a single-molecule transistor can be determined at liquid nitrogen temperatures by simply observing the IV characteristics. Abstract : The electronic and magnetic properties of single-molecule transistors depend critically on the molecular charge state. Charge transport in single-molecule transistors is characterized by Coulomb-blocked regions in which the charge state of the molecule is fixed and current is suppressed, separated by high-conductance, sequential-tunneling regions. It is often difficult to assign the charge state of the molecular species in each Coulomb-blocked region due to variability in the work-function of the electrodes. In this work, we provide a simple and fast method to assign the charge state of the molecular species in the Coulomb-blocked regions based on signatures of electron–phonon coupling together with the Pauli-exclusion principle, simply by observing the asymmetry in the current in high-conductance regions of the stability diagram. We demonstrate that charge-state assignments determined in this way are consistent with those obtained from measurements of Zeeman splittings. Our method is applicable at 77 K, in contrast to magnetic-field-dependent measurements, which generally require low temperatures (below 4 K). Due to the ubiquity of electron–phonon coupling in molecular junctions, we expect this method to be widely applicable to single-electron transistors based on single molecules and graphene quantum dots. The correct assignment of charge states allows researchers to better understand the fundamental charge-transport properties of single-molecule transistors.